Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Ta có: \(5x^2-3x\left(x+2\right)\)
\(=5x^2-3x^2-6x\)
\(=2x^2-6x\)
b) Ta có: \(3x\left(x-5\right)-5x\left(x+7\right)\)
\(=3x^2-15x-5x^2-35x\)
\(=-2x^2-50x\)
c) Ta có: \(3x^2y\left(2x^2-y\right)-2x^2\left(2x^2y-y^2\right)\)
\(=3x^2y\left(2x^2-y\right)-2x^2y\left(2x^2-y\right)\)
\(=x^2y\left(2x^2-y\right)=2x^4y-x^2y^2\)
d) Ta có: \(3x^2\left(2y-1\right)-\left[2x^2\cdot\left(5y-3\right)-2x\left(x-1\right)\right]\)
\(=6x^2y-3x^2-\left[10x^2y-6x^2-2x^2+2x\right]\)
\(=6x^2y-3x^2-10x^2y+6x^2+2x^2-2x\)
\(=-4x^2y+5x^2-2x\)
e) Ta có: \(4x\left(x^3-4x^2\right)+2x\left(2x^3-x^2+7x\right)\)
\(=4x^4-16x^3+4x^4-2x^3+14x^2\)
\(=8x^4-18x^3+14x^2\)
f) Ta có: \(25x-4\left(3x-1\right)+7x\left(5-2x^2\right)\)
\(=25x-12x+4+35x-14x^3\)
\(=-14x^3+48x+4\)
bài 1
a) \(-\frac{1}{3}xy\).(3\(x^2yz^2\))
=\(\left(-\frac{1}{3}.3\right)\).\(\left(x.x^2\right)\).(y.y).\(z^2\)
=\(-x^3\).\(y^2z^2\)
b)-54\(y^2\).b.x
=(-54.b).\(y^2x\)
=-54b\(y^2x\)
c) -2.\(x^2y.\left(\frac{1}{2}\right)^2.x.\left(y^2.x\right)^3\)
=\(-2x^2y.\frac{1}{4}.x.y^6.x^3\)
=\(\left(-2.\frac{1}{4}\right).\left(x^2.x.x^3\right).\left(y.y^2\right)\)
=\(\frac{-1}{2}x^6y^3\)
Bài 3:
a) \(f\left(x\right)=-15x^2+5x^4-4x^2+8x^2-9x^3-x^4+15-7x^3\)
\(f\left(x\right)=\left(5x^4-x^4\right)-\left(9x^3+7x^3\right)-\left(15x^2+4x^2-8x^2\right)+15\)
\(f\left(x\right)=4x^4-16x^3-11x^2+15\)
b)
\(f\left(x\right)=4x^4-16x^3-11x^2+15\)
\(f\left(1\right)=4\cdot1^4-16\cdot1^3-11\cdot1^2+15\)
\(f\left(1\right)=4\cdot1^4-16\cdot1^3-11\cdot1^2+15\)
\(f\left(1\right)=-8\)
\(f\left(x\right)=4x^4-16x^3-11x^2+15\)
\(f\left(-1\right)=4\cdot\left(-1\right)^4-16\cdot\left(-1\right)^3-11\cdot\left(-1\right)^2+15\)
\(f\left(-1\right)=24\)
\(A=4x^4+7x^2y^2+3y^4+5y^2\)
\(A=4x^4+4x^2y^2+3x^2y^2+3y^4+5y^2\)
\(A=4x^2.\left(x^2+y^2\right)+3y^2.\left(x^2+y^2\right)+5y^2\)
\(A=4x^2.5+3y^2.5+5y^2\)
\(A=5.\left(4x^2+3y^2+y^2\right)\)
\(A=5.\left(3x^2+3y^2+x^2+y^2\right)\)
\(A=5.\left(3.\left(x^2+y^2\right)+(x^2+y^2)\right)\)
\(A=5.\left(3.5+5\right)\)
\(A=5.20\)
\(A=100\)
CHÚC BN HỌC TỐT!!!!
A = 4x4 + 7x2y2 + 3y4 + 5y2
= 4x4 + 4x2y2 + 3x2y2 + 3y4 + 5y2
= 4x2(x2 + y2) + 3y2(x2 + y2) + 5y2
= 4x2 . 5 + 3y2 . 5 + 5y2
= 20x2 + 15y2 + 5y2
= 20x2 + 20y2
= 20(x2 + y2)
= 20 . 5
= 100
Thái Viết Nam
Với x2 + y2 = 5
Ta có:
A = 4x4 + 7x2 y2 + 3y4 + 5y2
= 4x4 + 4x2 y2 + 3x2 y2 + 5y2
= 4x2 . ( x2 + y2 ) + 3y2 . ( x2 + y2 ) + 5y2
= 4x2 . 5 + 3y2 . 5 + 5y2
= 20x2 + 15y2 + 5y2
= 20x2 20y2 = 20. ( x2 + y2 ) = 20 . 5 = 100
Vậy A = 100
^^ Học tốt!
\(A=4x^4+7x^2y^2+3y^4+5y^2=\left(4x^4+4x^2y^2\right)+\left(3x^2y^2+3y^4\right)+5y^2\)
\(=4x^2\left(x^2+y^2\right)+3y^2\left(x^2+y^2\right)+5y^2=20x^2+20y^2\)
\(=20\left(x^2+y^2\right)=20.5=100\)
1: \(=3x^4+3x^2y^2+2x^2y^2+2y^4+2y^2\)
\(=\left(x^2+y^2\right)\left(3x^2+2y^2\right)+2y^2\)
\(=3x^2+2y^2+2y^2=3x^2+4y^2\)
2: \(=7\left(x-y\right)+4a\left(x-y\right)-5\)
=-5
3: \(=\left(x-y\right)\left(x^2+xy+y^2\right)-xy\left(x-y\right)+3=3\)
4: \(=\left(x+y\right)^2-4\left(x+y\right)+1=9-12+1=-2\)
\(=7x^2+7x^2y^2+35y^2\)
\(=7.\left[x^2.\left(x^2+y^2\right)\right]+35y^2\)
\(=7.x^2.5+35y^2\)
\(=35x^2+35y^2\)
=\(35.\left(x^2+y^2\right)\)
=35.5=175